IMPLEMENTATION OF THE SYIRKAH ABDAN AGREEMENT IN COOPERATION BETWEEN MAKEUP ARTISTS AND TENT ENTREPRENEURS IN PERCUT SEI TUAN DISTRICT, DELI SERDANG REGENCY FROM THE PERSPECTIVE OF THE HANAFI SCHOOL - Rizka Putri Agustina Siregar; Fatimah Zahara (Program Pascasarjana UIN Sumatera Utara, 2025)
This research is motivated by the existence of cooperation practices carried out by party vendors such as cooperation between makeup artists and tent entrepreneurs in Percut Sei Tuan District, Deli Serdang Regency. This cooperation is usually carried out verbally or informally, namely via cellphone or via WhatsApp and there is no written agreement in it so that it often triggers disputes such as payment problems and others. This study aims to analyze how the implementation of the syirkah abdan contract in cooperation between makeup artists and tent entrepreneurs in Percut Sei Tuan District, Deli Serdang Regency and examine it from the perspective of the Hanafi school of thought. The syirkah contract in this cooperation is a form of service-based business partnership, namely each party contributes from their work or expertise. The research method used is empirical juridical by examining the practice of cooperation that occurs directly in the community using interview data collection techniques, observations and documentation studies to obtain primary and secondary data. Based on the results of the study, it shows that the practice of syirkah abdan in this area is usually carried out verbally so that it is prone to causing disputes. The implementation of syirkah abdan in this area is considered legally syar'i when it fulfills the elements of ijab qabul and joint contribution according to the Hanafi school of thought. However, breaking the agreement by one of the parties, such as running away and taking the profits, makes the agreement on this collaboration fasakh (void) and the aggrieved party has the right to claim its rights through a dispute resolution mechanism (qadha). The recommendation from this research is the need to form a written contract in an agreement as well as a deep understanding of muamalah fiqh law in order to avoid disputes in collaborative activities.